Analisis faktor-faktor yang mempengaruhi pengelolaan manajemen logistik terhadap kinerja anggota Ditsamapta dalam menjaga Kamtibmas Wilayah Polda Kalimantan Selatan - Gunawan, Azis; Soegiri, Hary (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of the study was to determine and analyze logistical factors such as human resources, transportation, distribution center locations, product availability and communication simultaneously and partially on the performance of members and the dominant influence of these independent variables on the performance of members of the Ditsamapta Polda South Kalimantan in Maintaining Kantibmas Regional Police South Kalimantan. Population and sample of 67 respondents are members of Ditsamapta. Types of quantitative data with multiple regression analysis.The results showed that logistical factors such as human resources, transportation, distribution center location, product availability and communication had a simultaneous significant effect on the performance of members, then logistical factors such as human resources, transportation, distribution center location, product availability and communication had a partially significant effect on the performance of members and logistical factors such as product availability have a dominant effect on the performance of members of the Ditsamapta Polda South Kalimantan in Maintaining Kamtibmas for the Regional Police of South Kalimantan.